Development and Evaluation of the Rapid and Sensitive RPA Assays for Specific Detection of Salmonella spp. in Food Samples - Zhao, Liwei; Wang, Jianchang; Sun, Xiao Xia; Wang, Jinfeng; Chen, Zhimin; Xu, Xiangdong; Dong, Mengyuan; Guo, Ya-nan; Wang, Yuanyuan; Chen, Pingping; Gao, Weijuan; Geng, Yunyun (Frontiers in Cellular and Infection Microbiology, 2021)
Salmonella spp. is among the main foodborne pathogens which cause serious foodborne diseases. An isothermal real-time recombinase polymerase amplification (RPA) and lateral flow strip detection (LFS RPA) were used to detect Salmonella spp. targeting the conserved sequence of invasion protein A (invA). The Real-time RPA was performed in a portable florescence scanner at 39°C for 20 min. The LFS RPA was performed in an incubator block at 39°C for 15 min, under the same condition that the amplifications could be inspected by the naked eyes on the LFS within 5 min. The detection limit of Salmonella spp. DNA using real-time RPA was 1.1 × 101 fg, which was the same with real-time PCR but 10 times higher than that of LFS RPA assay. Moreover, the practicality of discovering Salmonella spp. was validated with artificially contaminated lamb, chicken, and broccoli samples. The analyzing time dropped from 60 min to proximately 5–12 min on the basis of the real-time and LFS RPA assays compared with the real-time PCR assay. Real-time and LFS RPA assays’ results were equally reliable. There was no cross-reactivity with other pathogens in both assays. In addition, the assays had good stability. All of these helped to show that the developed RPA assays were simple, rapid, sensitive, credible, and could be a potential point-of-need (PON) test required mere resources.